Peran Keluarga dalam Mendukung Pendidikan Agama Islam Anak SD: Suatu Analisis Kualitatif - Khoirun Nisa (JURNAL RISET RUMPUN ILMU PENDIDIKAN, 2022)
Islamic education at the Elementary School (SD) level significantly impacts the formation of character and morality in children. This research focuses on the role of the family in supporting Islamic education at the SD level, identifying parents' perceptions, the family's role in reinforcing Islamic values in children, and the challenges faced by families in supporting Islamic education in the modern era. The research method used is a qualitative-literature approach.. The conclusion of this research provides a profound understanding of the dynamics of the relationship between the family and Islamic education at the SD level. These findings can contribute to educators, parents, and policymakers in creating an educational environment that supports the holistic development of children, especially in understanding the vital role of the family in supporting Islamic education at the SD level.